Rapamycin Promotes the Expansion of Myeloid Cells by Increasing G-CSF Expression in Mesenchymal Stem Cells - Li, Minghao; Lan, Yanjie; Gao, Juan; Yuan, Shengnan; Hou, Shuaibing; Guo, Tengxiao; Zhao, Fei; Wang, Yuxia; Yuan, Weiping; Wang, Xiaomin (Frontiers in Cell and Developmental Biology, 2022)
Rapamycin, also known as sirolimus, an inhibitor of mammalian target of rapamycin (mTOR), is a regulatory kinase responsible for multiple signal transduction pathways. Although rapamycin has been widely used in treating various hematologic diseases, the effects of rapamycin are still not fully understood. Here we found that both oral and intraperitoneal administration of rapamycin led to the expansion of myeloid lineage, while intraperitoneal administration of rapamycin impaired granulocyte differentiation in mice. Rapamycin induced bone marrow mesenchymal stem cells to produce more G-CSF in vitro and in vivo, and promoted the myeloid cells expansion. Our results thus demonstrated that high dose of rapamycin might promote the expansion of myeloid lineage while impair myeloid cell differentiation in vivo.